Criminal Law Policy Expires on Criminal Acts of Corruption - Achmad Eka Yougi Ardata; Moh. Muhibbin; Budi Parmono (Universitas Internasional Batam, 2025)
This research is motivated by the increasing number of cases of criminal acts of corruption in Indonesia. One of the reasons behind this is the implementation of the statute of limitations, so that many corruptors remove traces of not taking responsibility for the criminal acts they have committed. The aim of this research is to determine and analyze criminal law regulations and policies regarding the statute of limitations in criminal acts of corruption. This research uses normative juridical methods. The results of this research are that the statute of limitations for criminal acts of corruption has not been specifically regulated in the Law on the Eradication of Corruption Crimes. So that in its implementation it is based on 2 regulations with provisions, namely a minimum state loss of IDR 1,000,000,000. Article 40 of Law Number 19 of 2019 applies, namely an expiry period of 2 (two) years. Meanwhile, losses resulting from criminal acts of corruption are below IDR 1,000,000,000, Article 78 of the Criminal Code applies, based on the Corruption Eradication Law, which states that the criminal threat consists of a minimum imprisonment of one years and a maximuam of twenty years, as well as life imprisonment, then the applicable expiry times are six years, twelve years and eighteen years. Therefore, a new legal instrument is required to ensure legal certainty by specifically regulating expiration periods for corruption crimes. Furthermore, the loss of criminal liability due to expired provisions undermines justice and disadvantages both the state and society, which suffer losses from such acts.Therefore, a new legal instrument is required to ensure legal certainty by specifically regulating expiration periods for corruption crimes. Furthermore, the loss of criminal liability due to expired provisions undermines justice and disadvantages both the state and society, which suffer losses from such acts.